The Influence of Information System Quality and Shopee's Digital Marketing Strategy on Changes in Online Shopping of Asahan University Students in 2025 - Marpaung, Putri Zalianty; Dailami, D.; Tobing, Aprilia Wulandari Br. Lumban; Massari, Windi; Mirna, Nursarro Sauma; Simanjuntak, Ardella Anggraini; Riyanti , Heni (Golden Ratio of Mapping Idea and Literature Format, 2026)
The development of digital technology has changed shopping behavior, especially among students, as the digital native generation. This study aims to analyze the influence of Shopee's information system quality and digital marketing strategy on changes in online shopping behavior among Asahan University students in 2025. The method used was quantitative with a causal associative approach. Data were collected through questionnaires and analyzed using F-tests, t-tests, and the coefficient of determination (R²). The results show that Shopee's information system quality and digital marketing strategy simultaneously and partially significantly influence changes in online shopping behavior among students. A fast and user-friendly system, along with digital promotions such as flash sales and personal discounts, increases shopping intensity and patterns. These findings emphasize the importance of technology and marketing synergy in shaping digital consumer behavior.